2022
DOI: 10.1002/mrm.29462
|View full text |Cite
|
Sign up to set email alerts
|

Self‐calibrated through‐time spiral GRAPPA for real‐time, free‐breathing evaluation of left ventricular function

Abstract: Purpose Through‐time spiral GRAPPA is a real‐time imaging technique that enables ungated, free‐breathing evaluation of the left ventricle. However, it requires a separate fully‐sampled calibration scan to calculate GRAPPA weights. A self‐calibrated through‐time spiral GRAPPA method is proposed that uses a specially designed spiral trajectory with interleaved arm ordering such that consecutive undersampled frames can be merged to form calibration data, eliminating the separate fully‐sampled acquisition. Theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…These techniques also can be paired with non-Cartesian trajectories to enable higher acceleration factors [53] , [54] . The need for additional calibration data can be avoided by using temporal SENSE/GRAPPA approaches, which derive the respective information from a sliding window reconstruction [53] , [55] , or by deploying self-calibration approaches [56] . K-t techniques use spatiotemporal redundancy of the data, where analysis of the frequency components (f) of the temporal evolution of a certain spatial position (x) in so-called x-f space can assist in the removal of respective aliasing artifacts before the data are transformed back into the k-t representation.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques also can be paired with non-Cartesian trajectories to enable higher acceleration factors [53] , [54] . The need for additional calibration data can be avoided by using temporal SENSE/GRAPPA approaches, which derive the respective information from a sliding window reconstruction [53] , [55] , or by deploying self-calibration approaches [56] . K-t techniques use spatiotemporal redundancy of the data, where analysis of the frequency components (f) of the temporal evolution of a certain spatial position (x) in so-called x-f space can assist in the removal of respective aliasing artifacts before the data are transformed back into the k-t representation.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] However, given the sensitivity of spiral sampling to B0 field inhomogeneity, the readout duration of single-shot spiral acquisitions is greatly limited, compromising the achievable spatial resolution. To improve the spatial resolution, single-shot spiral acquisitions can be combined with parallel imaging techniques, 17,18 resulting in shortened readout duration and alleviated static B0 off-resonance effects. With such a strategy, single-shot spiral acquisitions have been used to achieve high-resolution diffusion imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The number of arms was then varied from 50 to 3. Preliminary testing 23,24 suggested that acceleration factors of 8 or lower and TRs less than approximately 10 ms may yield acceptable image quality. Simulations of trajectories that met these specifications were performed, and those that resulted in visually similar image quality to the separately-calibrated reconstruction were tested in vivo for initial qualitative assessment.…”
Section: Trajectory Designmentioning
confidence: 99%